Russia, America and the Islamic world [ - Bowker, Mike (Aldershot, England;Burlington, VT : Ashgate, 2007)
With the ongoing conflict in Chechnya and upheavals in Kyrgyzstan and Uzbekistan, Islamic militancy has become a major security threat. This work examines the relationship between Russia and the United States in the fight against the common threat of international terrorism. it also looks at the difficulties of such a relationship
1. The post-Cold War world and the clash of civilisations -- 2. The Soviet war in Afghanistan -- 3. The Gulf War, 1990-1991. The wars in Yugoslavia : Bosnia and Kosovo -- 4. The conflict in Chechnya -- 5. 9/11 and the War on Terrorism -- 6. Gulf War II : Iraq 2003. Iran and nuclear proliferation -- 7. Israel and the Palestinian question -- 8. The Caucasus, Central Asia, and 'the coloured revolutions'. America
Includes bibliographical references (p 171-185) and index
Keywords: Iraq War, 2003-; Terrorism -- Government policy -- United States; War on Terrorism, 2001-; Iraq War, 2003-; Terrorism; War on Terrorism, 2001-; Islamic countries -- Foreign relations -- United States; Russia (Federation) -- Foreign relations -- United States; United States -- Foreign relations -- Islamic countries; United States -- Foreign relations -- Russia (Federation)